Analisis Pemanfaatan Literasi Digital Pada Mata Kuliah Pengembangan Bahan Ajar Digital Prodi Pendidikan Bahasa Indonesia Universitas Almuslim - Misqa, Laina; Astuti, Nia; Darwis, Muhammad (Universitas Negeri Padang, 2026)
This research aims to analyze the utilization of digital literacy in the Digital Teaching Materials Development course in the Indonesian Language Education Study Program at Almuslim University. Digital literacy has become an important skill in 21st-century education, encompassing the ability to access, evaluate, utilize, and create digital information ethically and effectively. This study employs a qualitative method with a descriptive approach, using data collection techniques such as observation, questionnaires, and documentation. Data analysis is conducted using content analysis, which involves examining and interpreting data in-depth to identify patterns and meanings based on five indicators of digital literacy: technology access, information searching, collaboration, digital ethics, and information evaluation. The results indicate that students have utilized digital literacy quite well in the development of teaching materials. They have access to digital devices and are able to use various platforms like Canva, Kahoot, and Learning Management System. Students' responses also indicate a positive attitude towards the process of developing digital teaching materials, particularly in terms of conceptual understanding. This is reflected in the average response placing them in the agree category. This study concludes that digital literacy plays a crucial role in enhancing the quality of digital teaching material development, but ongoing guidance is still needed to improve students' critical and ethical thinking skills in a digital environment.